eAccess to Justice - Benyekhlef, Karim; Bailey, Jane; Burkell, Jacquelyn; Gélinas, Fabien (University of Ottawa Press, 2016)
Part I of this work focuses on the ways in which digitization projects can affect fundamental justice principles. It examines claims that technology will improve justice system efficiency and offers a model for evaluating e-justice systems that incorporates a broader range of justice system values. The emphasis is on the complicated relationship between privacy and transparency in making court records and decisions available online.Part II examines the implementation of technologies in the justice system and the challenges it comes with, focusing on four different technologies: online court information systems, e-filing, videoconferencing, and tablets for presentation and review of evidence by jurors. The authors share a measuring enthusiasm for technological advances in the courts, emphasizing that these technologies should be implemented with care to ensure the best possible outcome for access to a fair and effective justice system.Finally, Part III adopts the standpoints of sociology, political theory and legal theory to explore the complex web of values, norms, and practices that support our systems of justice, the reasons for their well-established resistance to change, and the avenues and prospects of eAccess. The chapters in this section provide a unique and valuable framework for thinking with the required sophistication about legal change.Published in English.

Le droit maritime dans tous ses états : Hommage méditerranéen à Pierre Bonassies, Philippe Delebecque et Christian Scapel - El Khayat, Mustapha (Presses universitaires d’Aix-Marseille, 2016)
Les échanges internationaux sont à dominante maritime. Ces échanges maritimes sont régis par des droits, en particulier le droit maritime et de la mer. Les relations entre chargeurs et transporteurs, fréteur-affréteurs et entre États ont donné lieu avec le temps à des conventions internationales pour harmoniser les droits maritimes et de la mer entre les nations. Des doctrines ont été forgées avec le temps par d’éminents juristes qui ont essayé de contribuer au développement d’un droit maritime et de la mer moderne et évolutif. En France, Pierre Bonassiès, Christian Scapel et Philippe Delebecque en sont parmi les précurseurs. Cet ouvrage est rédigé en leur honneur et permet au lecteur, qu’il soit chercheur, praticien ou étudiant de plonger dans les débats majeurs du droit maritime dans ses états.
Code: Le droit maritime dans tous ses états : Hommage méditerranéen à Pierre Bonassies, Philippe Delebecque et Christian Scapel Publication Title: Le droit maritime dans tous ses états : Hommage méditerranéen à Pierre Bonassies, Philippe Delebecque et Christian Scapel Reporter: Le droit maritime dans tous ses états : Hommage méditerranéen à Pierre Bonassies, Philippe Delebecque et Christian Scapel Series Title: Droit maritime et des transports
Keywords: Droit de la mer; Droit de la responsabilité; Droit des transports; Droit international; Droit maritime; Transport de marchandises

Banking and financial insolvencies: the European regulatory framework - Parry, Rebecca; Omar, Paul J. (INSOL Europe, 2016)
IRep - Nottingham Trent University's open access institutional research repository
https://irep.ntu.ac.uk/id/eprint/28401/

Droits linguistiques et droit à la langue : identificationd'un objet d'étude et construction d'une approche - Potriquet, Ghislain; Huck, Dominique; Truchot, Claude (Lambert-Lucas, 2016)